PENGARUH PENERAPAN MODEL DISCOVERY LEARNING BERBANTU MEDIA VIDEO TERHADAP HASIL BELAJAR RANAH KOGNITIF - Aldila Aldila; Sri Sumaryati; Asri Diah Susanti (Universitas Sebelas Maret, 2022)
Abstract This study aims to determine an effect of the application of the discovery learning model assisted by video media on the learning outcomes of the cognitive domain of accounting students at SMK X. This research is a quantitative quasi experimental with a pretest-posttest control group design. Hypothesis tests are use independent sample t-test, paired sample t-test, and n-gain. The results of this study are the discovery learning model assisted by video media has not a significant effect based on idependent sample t-test and has a significant effect based on paired sample t-test to learning outcomes in the cognitive domain of accounting students at SMK X with a t-count value of 4.998> 2.04227 and an average n-gain of 0.3003. Keywords: Discovery learning, Video media, Cognitive learning outcomes, Accounting Abstrak Penelitian ini bertujuan untuk mengetahui pengaruh penerapan model discovery learning berbantu media video terhadap hasil belajar ranah kognitif siswa akuntansi di SMK X. Penelitian ini merupakan penelitian kuantitatif quasy experimental dengan desain penelitian pretest-posttest control group design. Uji hipotesis menggunakan independent sample t-test, paired sample ttest, dan n-gain. Hasil penelitian ini adalah model discovery learning berbantu media video tidak berpengaruh signifikan menurut uji independent sample t-test dan berpengaruh signifikan menurut uji paired sample t-test terhadap hasil belajar ranah kognitif siswa akuntansi di SMK X dengan nilai t hitung sebesar 4,998>2,04227 dan rata-rata n-gain sebesar 0,3003. Kata kunci: Discovery learning, Media video, Hasil belajar ranah kognitif, Akuntansi